PARTISIPASI KARANG TARUNA KECAMATAN PANCENG SEBAGAI POTENSI DAN SUMBER KESEJAHTERAAN SOSIAL - Hakim, Lukman (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2024)
The government, through the Ministry of Social Affairs of the Republic of Indonesia, has made efforts to improve social welfare for the community. However, in the field it was found that not all levels of society could experience it, as happened in Panceng District, so the participation of Karang Taruna as an extension of the government was needed. This research aims to describe how the participation of Karang Taruna in Panceng District is a potential and source of social welfare, what the supporting and inhibiting factors are, as well as the impacts resulting from this participation. Qualitative methods were chosen in this research. Interviewing the administrators of the Panceng District Karang Taruna, observing and documenting studies on social media pages and news portals containing the Panceng District Karang Taruna are ways to answer the questions and objectives of this research. This research found that the participation of Karang Taruna in Panceng District as a potential and source of social welfare is realized through capacity building facilities for Karang Taruna residents as well as various cross-sectoral social actions, such as in the environmental, educational, economic and social sectors. This research also found that the human resources owned by Karang Taruna in Panceng District were a supporting factor, and the inhibiting factor was the lack of optimal partnership and synergy between stakeholders. The realization of awareness, social responsibility and the establishment of strong cooperation between Karang Taruna residents are the impacts.